Bibliometric analysis and literature review of ecotourism: Toward sustainable development - Khanra Sayantan; Dhir Amandeep; Kaur Puneet; Mäntymäki Matti (Elsevier, 2022)
In recent decades, rising consumer interest in visiting relatively less commercialized natural destinations has facilitated the growth of ecotourism. Yet the research on ecotourism is fragmented, presenting gaps in the current understanding of this topic. This study performs a bibliometric analysis to assimilate the present knowledge from a total of 878 articles published in six reputable outlets between 1990 and 2019. The study analyzed citation chains and coauthorship networks to acknowledge contributions from select authors, organizations, and countries. Next, a cocitation analysis of the prior literature identified four major thematic areas: ecological preservation, residents' interests, the carbon footprint, and tourists' behaviors. Further, a dynamic cocitation analysis technique mapped the development of these thematic areas. Subsequently, a content analysis of the four thematic areas delivered significant insights about prior research in the domain and indicated future avenues of research.